Amyotrophy, cerebellar impairment and psychiatric disease are the main symptoms in a cohort of 14 Czech patients with the late-onset form of Tay-Sachs disease - Jahnová, Helena; Poupětová, Helena; Jirečková, Jitka; Vlášková, Hana; Košťálová, Eva; Mazanec, Radim; Zumrová, Alena; Mečíř, Petr; Mušová, Zuzana; Magner, Martin (Journal of neurology, 2019)
BACKGROUND: Tay-Sachs disease (TSD) is an inherited neurodegenerative disorder caused by a lysosomal β-hexosaminidase A deficiency due to mutations in the HEXA gene. The late-onset form of disease (LOTS) is considered rare, and only a limited number of cases have been reported. The clinical course of LOTS differs substantially from classic infantile TSD. METHODS: Comprehensive data from 14 Czech patients with LOTS were collated, including results of enzyme assays and genetic analyses. RESULTS: 14 patients (9 females, 5 males) with LOTS were diagnosed between 2002 and 2018 in the Czech Republic (a calculated birth prevalence of 1 per 325,175 live births). The median age of first symptoms was 21 years (range 10-33 years), and the median diagnostic delay was 10.5 years (range 0-29 years). The main clinical symptoms at the time of manifestation were stammering or slurred speech, proximal weakness of the lower extremities due to anterior horn cell neuronopathy, signs of neo- and paleocerebellar dysfunction and/or psychiatric disorders. Cerebellar atrophy detected through brain MRI was a common finding. Residual enzyme activity was 1.8-4.1% of controls. All patients carried the typical LOTS-associated c.805G>A (p.Gly269Ser) mutation on at least one allele, while a novel point mutation, c.754C>T (p.Arg252Cys) was found in two siblings. CONCLUSION: LOTS seems to be an underdiagnosed cause of progressive distal motor neuron disease, with variably expressed cerebellar impairment and psychiatric symptomatology in our group of adolescent and adult patients. The enzyme assay of β-hexosaminidase A in serum/plasma is a rapid and reliable tool to verify clinical suspicions.
Keywords: Ataxia; Cerebellum; Humans; Muscular Atrophy; lidé středního věku; kohortové studie; β-Hexosaminidase A; Female; mladý dospělý; dospělí; Proximal weakness of lower extremities; lidé; duševní poruchy; Cohort Studies; svalová atrofie; Adult; Tay-Sachs Disease; ženské pohlaví; Male; Tay-Sachsova nemoc; Middle Aged; GM2 gangliosidosis; Adolescent; Czech Republic; Mental Disorders; Young Adult; mozeček; Late-onset Tay–Sachs disease; věk při počátku nemoci; Česká republika; mužské pohlaví; Age of Onset; mladiství